Long-term CMV monitoring and chronic rejection in renal transplant recipients - Ishikawa, Shoko; Tasaki, Masayuki; Saito, Kazuhide; Nakagawa, Yuki; Ikeda, Masahiro; Takahashi, Kota; Tomita, Yoshihiko (Frontiers in Cellular and Infection Microbiology, 2023)
Cytomegalovirus (CMV) is well established to be an independent risk factor for graft loss after kidney transplantation (KTx). Monitoring for CMV in the chronic phase is not defined in the current guideline. The effects of CMV infection, including asymptomatic CMV viremia, in the chronic phase are unclear. We performed a single-center retrospective study to investigate incidence of CMV infection in the chronic phase, defined as more than 1 year after KTx. We included 205 patients who received KTx between April 2004 and December 2017. The CMV pp65 antigenemia assays to detect CMV viremia were continuously performed every 1–3 months. The median duration of the follow-up was 80.6 (13.1–172.1) months. Asymptomatic CMV infection and CMV disease were observed in 30.7% and 2.9% in the chronic phase, respectively. We found that 10–20% of patients had CMV infections in each year after KTx which did not change over 10 years. The history of CMV infection in the early phase (within 1 year after KTx) and chronic rejection were significantly associated with CMV viremia in the chronic phase. CMV viremia in the chronic phase was significantly associated with graft loss. Preventing latent CMV infection may decrease chronic rejection and graft loss.